THE EFFECT OF INCENTIVES ON THE PRODUCTIVITY OF IFIVE INDONESIA SALES PARTNERS - Muhammad Ramdhan (BAIK Publishers, 2024)
The purpose of this study was to determine the effect of incentives on the productivity of IFive Indonesia Sales Partners. The research method used in this study uses a quantitative approach. The population is 36 people. The sampling technique uses saturated samples so that the number of samples in this study is 36 respondents. The data analysis technique uses simple linear regression. The results of the study show that there is a positive and significant effect of the effect of incentives on the productivity of IFive Indonesia Sales Partners. This is evidenced by the tcount > ttable value, namely 6.638 > 2.032 with a probability value (significance) = 0.000, which is below 0.05.